"The Great Near." Mondi possibili in The Princess Steel di W.E.B. DuBois - Adriano Elia (Iperstoria, 2016)
W.E.B. Du Bois’s short storyThe Princess Steel(c. 1908) is a significant example of proto-Afrofuturist speculative fiction functioning as a powerful allegory on the origins of modern capitalistic industry. An original hybrid narrative form,The Princess Steelcombines to great effect disparate genres such as literary realism, romance and science fiction. Using a series of intertwining plots, Du Bois developed a clear-cut political statement that on the one hand, through irony, denounces the stigmatization of black people, and on the other, through the parable of the Princess Steel, prophetically directs acute criticism towards the degeneration of colonial exploitation and industrial capitalism.